Eksistensi Braga Permai Sebagai Salah Satu Ikon Kuliner Kota Bandung - Suminar , Retna; Efendi , Fadilah Intan; Nuriyati, Rifa; Putri, Syofianna; Hermansyah (Jurnal Pendidikan Kewarganegaraan dan Politik, 2024)
This research aims to explore the history and local wisdom related to Braga Permai, to its transformation from Maison Bogerijen to Braga Permai. The method used in this study is qualitative based on the data from the results of observations made to observe directly and the dynamics that occur in the field. As well as using literature studies to help researchers to understand existing theories by involving summarizing and analyzing information from various written sources, such as books, journal articles, and other relevant documents. With this qualitative approach, it is hoped that the research can produce more holistic and contextual findings, as well as make a meaningful contribution to the understanding of the phenomenon that Maison Bogerijen is being researched by Leendert van Bogerijen in 1918, which was originally the resting place of the French king and a gathering place for Dutch East Indies officials. The colonial era influenced various aspects of life, including culinary, with one of its culinary legacies being Braga Permai in Bandung. The restaurant retains elements of history, grand architecture, and a typical European menu, while adapting to the local culture by adding local menus and services. Its main attractions include its famous bread, bitterballen, tongue steak, and lamb chop.  The staff at maison bogerijen is known to be very responsive to visitors' requests and queries, many visitors report that this friendly service enhances their dining experience, making for enthusiasm and good knowledge. Its popularity is supported by word-of-mouth promotion and social media influence. Braga Permai emphasizes inclusivity, accepting customers from various walks of life, and maintaining original recipes.  With a commitment to maintaining cultural values and service quality, Braga Permai remains the main culinary destination in Bandung.